UPAYA MENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI METODE DISKUSI PADA SISWA KELAS VI SD NEGERI 24 INDRALAYA - Hudah, Nurul (Jurnal Ilmiah Bina Edukasi, 2019)
This study aims to improve student learning outcomes using the method of discussion on math in the 6th grade. The subjects in this study were 6th grade students of SD Negeri 24 Indralaya, totaling 27 students. This research was conducted in semester gazal 2019. The research used Classroom Action Research (CAR). This CAR consists of two cycles. The results showed of 27 students of 74, 07% achieved completeness of KKM 70 in Cycle 1. In Cycle II, students who achieved KKM 70 increased by 85.19% with an average grade of 82.59. So, it can be concluded that learning by using discussion methods can improve student learning outcomes in Mathematics